PENGARUH PENGHINDARAN PAJAK, PERSENTASE DAN MASSA KRITIS DIREKTUR WANITA TERHADAP NILAI PERUSAHAAN - Marmileni Triana; Robby Krisyadi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The value of a company is very important because the higher the level of business continuity, the prosperity of the stakeholders is also higher. This study aims to examine the effect of tax avoidance, the percentage of female directors, and the critical mass of female directors on firm value listed on the Indonesia Stock Exchange (IDX). The object of this research is companies listed on the Stock Exchange from 2016 to 2020. This study took samples using the purposive sampling method. The results of this study indicate that tax avoidance, percentage of female directors and critical mass of female directors have no significant effect on firm value.